Perceived Organizational Support dan Kinerja Pegawai: Peran Mediasi Komitmen Normatif Pada Aparatur Sipil Negara Pemerintah Daerah Kota Serang, Banten - Chaidir, John; Zulfikar, Taufik; Aprianti, Ine; Millah, Fadli Saepul (Universitas Mercu Buana, 2025)
This study aims to analyze the influence of Perceived Organizational Support (POS) on Employee Performance (EP), with Normative Commitment (NC) as a mediating variable. The research was conducted on civil servants (ASN) of the Serang City Government, Banten. The target population consisted of ASN with a minimum tenure of five years (N = 1,500). The sample size was determined using the Slovin/Taro Yamane formula with a margin of error of approximately 8.76 percent, resulting in 120 respondents. The sampling technique applied was probability sampling with a simple random sampling (SRS) approach, ensuring that every employee in the population had an equal chance of being selected. Data were collected using a structured questionnaire and analyzed with the PLS-SEM method through SmartPLS software. The results show that POS positively influences employee performance, while NC also plays a significant role in improving performance. Furthermore, NC mediates the influence of POS on employee performance, indicating that employees’ sense of obligation strengthens the effect of organizational support. These findings suggest that organizational practices such as fair treatment, adequate rewards, and concern for employee welfare are crucial in fostering responsibility, loyalty, and improved performance in public organizations.